2010
DOI: 10.1177/193758671000300306
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nature Images on Pain in a Simulated Hospital Patient Room

Abstract: Although there was no clear "most" therapeutic image, the mixed prospect and refuge image showed significant potential to reduce sensory pain. The hazard image was the most effective at distracting participants from pain, but it should not be considered a positive distraction because it also received the highest mood disturbance scores of all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
0
30
0
2
Order By: Relevance
“…Evolutionary theory underpins much research in the field of therapeutic landscape aesthetics (Vincent, Battisto, Grimes, & McCubbin, 2010), and interrelated evolutionary perspectives posit innate human preference for landscapes with features that support human well-being and survival. The current study utilizes Darwin's evolutionary theory, Appleton's prospect refuge theory, and Ulrich's psychoevolutionary theory to inform construction of the IFSS.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Evolutionary theory underpins much research in the field of therapeutic landscape aesthetics (Vincent, Battisto, Grimes, & McCubbin, 2010), and interrelated evolutionary perspectives posit innate human preference for landscapes with features that support human well-being and survival. The current study utilizes Darwin's evolutionary theory, Appleton's prospect refuge theory, and Ulrich's psychoevolutionary theory to inform construction of the IFSS.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…One review found that the effects of nature fall into three categories: short-term recovery from stress, recovery from illness, and long-term improvements in mood (Velarde et al, 2007). Viewing nature, either live or through photographs and videos, has been linked with a wide range effects, including increased relaxation as shown through EEG (Chang, 2002), decreased anxiety about surgery (Ulrich et al, 1993), increased heart rate variability (Gladwell et al, 2012), decreased job stress, increased life satisfaction (Kaplan et al, 1988), and decreased pain (Vincent et al, 2010;White et al, 2019). A recent study by White et al (2019) found that the optimal dose for improved health and well-being was 120 h of nature contact per week; however, the beneficial effects of nature have been found to occur within less than 5 minutes (Ulrich, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that when making comparisons between an experimental and control group, recorded, personally preferred music decreased 12 of 15 occurrences of identified aggressive behaviors by individuals with Alzheimer’s disease during bathing, 9 , 10 and another study revealed that preferred music improved mood and reduced agitation during bathing. 11 Nature views also have promise for reducing undesirable behaviors as they have been shown to reduce stress, anxiety, and pain, 12 19 which can manifest in undesirable behaviors of those with ADOD.…”
Section: Introductionmentioning
confidence: 99%